In vitro antibacterial activity of tigecycline against clinical isolates of Linezolid-Intermediate (LIE) and Linezolid-Resistant Enterococci (LRE) by time-kill assay - Sambrano, Gustavo Enck; Paim, Thiago Galvão da Silva; da Silva, Lucas Toniolo; d’Azevedo, Pedro Alves (Clinical and Biomedical Research, 2014)
Introduction: Enterococci have become the third major leading cause of nosocomial bacteraemia, an infection which is significantly associated with the risk of developing infective endocarditis. Linezolid provides high rates of clinical cure and microbiologic success in complicated infections due to Enterococcus spp. However, several instances of emergence of resistance during linezolid treatment have been reported. The aim of this study was evaluate the activity of tigecycline against Linezolid-Intermediate (LIE) and Linezolid-Resistant Enterococcus faecalis (LRE) by the time-kill assay. Methods: Five isolates of LRE and two isolates of LIE were used in this study. MICs were determined by broth dilution following the CLSI (2014) guidelines. Time-kill assay was employed to access the in vitro response profile of tigecycline. Results: All seven of the isolates presented MIC of 0.125μg/mL. Tigecycline activity was individually evaluated and in three of the five isolates of LRE it presented bactericidal. Against the other isolates, tigecycline showed bacteriostatic activity. The tigecycline activity was measured according to CLSI criteria. Conclusions: Tigecycline presented both bacteriostatic and bactericidal activity against tested isolates, result not yet described in previous studies. Time and concentrations above MIC were key factors to achieving bactericidal effect. MIC and the tested concentration below it resulted in bacteriostatical effect to enterococci, corroborating previous data.